THU0096 Serum Inflammation Identifies Increased Risk of Frailty in Rheumatoid Arthritis. (15th July 2016) - Andrews, J.; Wahl, E.; Schmajuk, G.; Yelin, E.; Katz, P.
Abstract : Background: Frailty is defined as "excess vulnerability to stressors, with reduced ability to maintain or regain homeostasis after a destabilizing event" 1 . Frailty is closely related to body composition and physical functioning, and is associated with increased risk of poor health outcomes including death. Serum inflammation is associated with differences in body composition and physical functioning in the general population and individuals with chronic disease. The ability of serum markers of inflammation to identify increased frailty among individuals with rheumatoid arthritis (RA) is unknown. Objectives: We tested whether serum erythrocyte sedimentation rate (ESR) and C-Reactive Protein (CRP) are associated with increased risk of frailty among men and women with RA. Methods: Participants were individuals in a longitudinal RA cohort. ESR and high sensitivity CRP were assessed from blood samples using standard clinical assays. Individuals with 3 or more of the following physical deficits were classified as frail 1 : 1) body mass index ≤18.5, 2) low grip strength (adjusted for sex and BMI, measured by handheld dynamometer), 3) severe fatigue (measured by the Fatigue Severity Inventory), 4) slow 4-meter walking speed (adjusted for sex and height), 5) low physical activity (measured by the International Physical Activity Questionnaire). Individuals with 1 or 2 deficits were classified as pre-frail, and those with no deficits as robust. 1 Multinomial logistic regression analyses controlling for age, sex, smoking status, RA disease duration, prednisone use, tumor necrosis factor inhibitor use, appendicular lean mass, and pain modeled the effects of ESR and CRP on severity of frailty. Results: Of the 141 participants, 60% were female; mean age was 58 (±11) years, duration of RA was 19 (±11) years, ESR was 19 (±19) mm/h, and hsCRP was 5 (± 8) mg/L. Sixteen participants (11%) were frail, 86 (61%) pre-frail, 22 (16%) robust, and 17 (12%) were missing grip strength data. In adjusted models, higher ESR was associated with significantly increased risk of frailty (Table 1 ). Similar trends were observed between CRP and risk of frailty, but did not reach statistical significance in adjusted models. Conclusions: Frailty and pre-frailty were common in our cohort of individuals with RA, with a greater prevalence than that of geriatric populations. ESR levels were associated with approximately twice the risk of being frail or pre-frail compared to being robust. CRP demonstrated similar effects on risk of frailty, though trends did not reach statistical significance. These findings underscore the burden of frailty among individuals with RA, and they may suggest a clinical role for serum ESR and CRP to identify individuals with RA at greatest risk of frailty. References: Fried J Am Geriatr Soc 2001;56:M146 Disclosure of Interest: None declared